Pengembangan Varian Produk Susu Kedelai Berdasarkan Preferensi Konsumen Dengan Menggunakan Metode Quality Function Deployment (QFD) - Hakim, Budi Lukman; Tamara, Doni Rafli (Jurnal Kalibrasi, 2024)
The purpose of this research is to develop soy milk products that are cheap and have many flavors and design a profitable soy milk business. The method used to achieve these two objectives is Quality Function Deployment. To design a soy milk business is done by distributing customer desire questionnaires as preferences for making soy milk products. The results of the study found that the development of powdered soy milk products with the SOYku brand resulted in 5 new flavor variants, namely chocolate, strawberry, vanilla, mango and original. With the cost of goods produced is Rp.3,168. In the cost of goods this product is obtained a profit of 20% of the total sales. Furthermore, SOYku's soy milk product business will get maximum profit if it sells 42 sachets per day with . Production is carried out together with one workforce able to get a daily production capacity of 50 sachets.